A Simple Numeric Set-Theoretical Method of the Logic Differential Calculus - Rytsar, B.Ye. (Управляющие системы и машины, 2016)
Предложен новый метод логического дифференциального исчисления на основании числового теоретико-множественного подхода к определению разных типов логических производных произвольного порядка от булевой функции. Алгоритм имеет относительно меньшую вычислительную сложность при меньшем количестве операций, необходимых для решения задачи, что подтверждено примерами определения разных логических производных произвольных порядков от функций, заимствованных авторами из известных публикаций в порядке сравнения с предложенным методом. Запропоновано новий метод логічного диференційного числення на основі числового теоретико-множинного підходу до визначення різних типів логічних похідних довільного порядку від бульової функції. Алгоритм має відносно меншу обчислювальну складність за меншої кількості операцій, необхідних для розв'язання задачі, що підтверджено прикладами визначення запропонованим методом різних логічних похідних довільних порядків від функцій, запозичених авторами з відомих публікацій з метою порівняння з пропонованим методом. A new method of the logic differential calculus, based on the numeric set-theoretical approach for the definition of the different logic derivatives types of the arbitrary order for Boolean function is proposed. The given algorithm has relatively less computational complexity due to the lower amount of the operations required for solving the given problem. This is proved in the given examples borrowed from the well-known publications, in order to compare them with the proposed numeric set-theoretic method to obtain the different types of logic derivatives of arbitrary order.